Inferior Vena Cava Duplication: Incidental Case in a Young Woman. (27th April 2016) - Coco, Danilo; Cecchini, Sara; Leanza, Silvana; Viola, Massimo; Ricci, Stefano; Campagnacci, Roberto
Abstract : A case of a double inferior vena cava (IVC) with retroaortic left renal vein, azygos continuation of the IVC, and presence of the hepatic portion of the IVC drained into the right renal vein is reported and the embryologic, clinical, and radiological significance is discussed. The diagnosis is suggested by multidetector computed tomography (MDCT), which reveals the aberrant vascular structures. Awareness of different congenital anomalies of IVC is necessary for radiologists to avoid diagnostic pitfalls and they should be remembered because they can influence several surgical interventions and endovascular procedures.